2023
DOI: 10.3390/plants12040708
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Soil Management: Effects of Clinoptilolite and Organic Compost Soil Application on Eco-Physiology, Quercitin, and Hydroxylated, Methoxylated Anthocyanins on Vitis vinifera

Abstract: Climate change and compostinS1g methods have an important junction on the phenological and ripening grapevine phases. Moreover, the optimization of these composting methods in closed-loop corporate chains can skillfully address the waste problem (pomace, stalks, and pruning residues) in viticultural areas. Owing to the ongoing global warming, in many wine-growing regions, there has been unbalanced ripening, with tricky harvests. Excessive temperatures in fact impoverish the anthocyanin amount of the must while… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 141 publications
1
3
0
Order By: Relevance
“…Instead, quercetin 3-glucoside (flavonol-glycoside) enhanced with exposure to solar radiation [147]. These results were confirmed by other authors [132,133]; high quantities were found of quercetin-3-O-glucoside and quercetin-3-O-glucuronide in stressed grapes. Vijay and Vadewki [167], in their experiment on Cabernet Sauvignon grapes, explained the benefit of uncovered clusters to solar light; in treated clusters (leaf removal, cluster thinning, and shoot thinning) higher concentrations of flavan-3-ols (i.e., catechin and epicatechin) and flavonols (i.e., quercetin and myricetin) were found (quercetin accumulation could be a light solar-dependent process).…”
Section: Solar Radiation and Uv-b Lightsupporting
confidence: 78%
See 2 more Smart Citations
“…Instead, quercetin 3-glucoside (flavonol-glycoside) enhanced with exposure to solar radiation [147]. These results were confirmed by other authors [132,133]; high quantities were found of quercetin-3-O-glucoside and quercetin-3-O-glucuronide in stressed grapes. Vijay and Vadewki [167], in their experiment on Cabernet Sauvignon grapes, explained the benefit of uncovered clusters to solar light; in treated clusters (leaf removal, cluster thinning, and shoot thinning) higher concentrations of flavan-3-ols (i.e., catechin and epicatechin) and flavonols (i.e., quercetin and myricetin) were found (quercetin accumulation could be a light solar-dependent process).…”
Section: Solar Radiation and Uv-b Lightsupporting
confidence: 78%
“…This probably happened owing to its ability to be an inert mineral able to reduce canopy surface temperatures as well as being radiation-reflecting. Other authors found an increase in extractable anthocyanins together with a reduction in quercetin forms in plants treated with soil applications of clinoptilolite [132,133]. This could be attributable to the ability of zeolites to mitigate water stress and allow for balanced ripening in extremely dry years.…”
Section: Kaolinmentioning
confidence: 91%
See 1 more Smart Citation
“…When drought stress occurs, plants exhibit an inherent ability to adapt to this water-deficient environment through various regulatory mechanisms. The repercussions of drought stress on plants can be evaluated by monitoring physiological or biochemical indicators [ 9 ]. The enhancement of photosynthetic physiological performance facilitates the accumulation of organic matter in plants [ 10 ].…”
Section: Introductionmentioning
confidence: 99%